Symbiotic bacteria and the structural specializations in the ileum of Cephalotes ants - Bution, Murillo L.; Caetano, Flávio Henrique [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Light, scanning, and transmission electron microscopy were used to examine the ultramorphology and ultrastructure of the ileum of Cephalotes atratus, Cephalotes clypeatus, and Cephalotes pusillus. Sections along the ileum revealed differences among the three main regions: proximal (or pylorus), medial, and distal. The structural specializations present in the ileum of these three ants have implications especially to the symbiotic bacteria harbored in this region of the digestive tract. The structural similarities are conspicuous for the three species examined, suggesting that this is the pattern adopted by the genus Cephalotes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Ultrastructure; Ileum; Symbionts; Cephalotes; Ants